Transcultural validation of Activities Scale for Kids (ASK): translation and pilot test - Fabbri, Lucia; Neviani, Rita; Festini, Filippo; Costi, Stefania (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The Activities Scale for Kids performance (ASKp) is one of the few self-assessment questionnaires in pediatric rehabilitation that measures child perception in performance of daily routine activities. ASKp is composed of 30 questions designed to explore activities and participation in children and teenagers with musculoskeletal disorders. Scores assess level of physical ability, identify appropriate treatment and monitor changes over time. We undertook this cross-cultural validation study to achieve a culturally adapted Italian version of ASKp, to be tested on Italian children. Methods: ASKp was converted into Italian by two independent certified translators, supported by two Italian research physiotherapists. Twelve children with musculoskeletal disorders, their parents and eleven expert pediatric physiotherapists independently assessed clarity of language and semantics of each item. Physiotherapists also evaluated content validity of each item. Results: One item out of 30 did not reach inter-rater agreement ≥80% for clarity and was modified according to suggestions given. A panel of three research physiotherapists improved clarity of some other items based on suggestions from study participants. Regarding content validity of ASKp, I-CVI was ≥0.59 for all items and overall ASKp was deemed valid (S-CVI/Ave 0.93). Conclusions: The Italian version of ASKp is linguistically clear and culturally coherent with a high content validity. It can be extremely useful in assessing activity limitation perspectives in Italian children and adolescent ranging from five to 15 affected by musculoskeletal disorders.